Behaviour change and social blinkers? The role of sociology in trials of self‐management behaviour in chronic conditions. Issue 2 (February 2014) - Ong, Bie Nio; Rogers, Anne; Kennedy, Anne; Bower, Peter; Sanders, Tom; Morden, Andrew; Cheraghi‐Sohi, Sudeh; Richardson, Jane C.; Stevenson, Fiona
Abstract Individual‐focused self‐management interventions are one response to both an ageing society and the purported increase in chronic conditions. They tend to draw on psychological theories in self‐management interventions, but over‐reliance on these theories can reinforce a narrow focus on specified attitudinal and behavioural processes, omitting aspects of living with a chronic condition. While advances have been made in health behaviour change theory and practice, scant attention has been paid to the social, with the question of social context remaining under‐theorised and under‐explored empirically. This is particularly noticeable in trials of behaviour change interventions for self‐management. The common sociological critique is that these ignore context and thus no explanation can be given as to why, for whom and under what circumstances a treatment works. Conversely, sociologists are criticised for offering no positive suggestions as to how context can be taken into account and for over‐emphasising context with the risk of inhibiting innovation. This article provides an overview of these issues and provides examples of how context can be incorporated into the rigid method of trials of self‐management for chronic conditions. We discuss modifications to both trial interventions and design that make constructive use of the concept of context.